Przedsiębiorstwo rolne we włoskim systemie prawnym (II) - Szymecka, Agnieszka (Wydawnictwo Naukowe UAM, 2008)
An agricultural enterprise as a legal category is regulated in Italian law by the provisions of Art. 2135 of the civil code o f 1942. That article provides for a definition of an agricultural entrepreneur. Pursuant to those provisions, an agricultural enterprise is any form of land cultivation, forestry, animal breeding and related activity conducted in an organised and professional manner. While the first three activities are of agricultural character by nature and as such they justify the special status o f an agricultural enterprise, the latter include commercial or industrial activities which the Italian legislator decided, for different reasons, to treat as agricultural due to their nature. The paper aims to analyse different aspects of related activities in order to identify the above categories, their qualifying criteria and types of such activity in order to subsequently divide them into activities with an impact on agricultural produce exercised with a view of its better positioning in the market, and activities focused of the provision of certain goods and services. The evolution of different solutions and their development is also discussed. The paper ends with an overall assessment of an agricultural enterprise as such and on that basis certain conclusions and postulates addressed to the Polish legislator are offered.

La nozione giuridica di impresa agricola nel diritto italiano viene ricavata dall’art. 2135 del códice civile del 1942, il quale detta la definizione dell'imprenditore agricolo. Alia luce di questa norma, per impresa agricola si intende la coltivazione del fondo, la silvicoltura, l’allevamento di animali e le attivitá connesse. Le prime tre delle suindicate attivitá hanno carattere agricolo e giustificano lo status giuridico privilegiato dell'impresa agricola. Le attivitá connesse sono invece le attivitá di carattere commerciale o industríale che per vari motivi il legislatore italiano ha equiparato alie attivitá agricole di natura. L ’obbiettivo dell'artico lo é la presentazione al Lettore polacco della problemática delle attivitá connesse. In particolare vengono analizzati gli obiettivi dell’individuazione di una tale categoría di attivitá, i criteri di qualificazione di queste attivitá, nonché la loro classifícazione a seconda che abbiano come scopo la migliore collocazione sul mercato dei prodotti agricoli (attraverso la loro valorizzazione, trasformazione, ecc.) o siano orientate alia fornitura di beni e servizi. Viene illustrata anche l’evoluzione delle regolazioni normative in questa materia. In conclusione si propone una valutazione generale della categoría di impresa agricola e in base a quest’ultima si formulano le proposte di riforma del diritto polacco.
Agricultural enterprise in the Italian legal system (II)
L'impresa agricola nel sistema giuridico italiano (parte II)